Efektivitas Teknik Sosiodrama Untuk Meningkatkan Komunikasi Interpersonal Siswa (Penelitian Kuasi Eksperimen Kelas X di SMA Kartika Siliwangi 2 Bandung Tahun Ajaran 2013/2014) - Evi Zuhara (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2015)
Adolescence is a period of social adolescence because all social relationships is becoming more obvious and very dominant. Social relationship will be established with good interpersonal communication when there is in it. Students who have difficulty in interpersonal communication will be difficult to adjust themselves, tend to be overbearing, selfish, and want to win themselves so easily involved in the dispute. The aim of this research is intended to establish the effective interventions to improve students' interpersonal communication. The main of research problem was